Implementasi dan Sejarah Hukum Islam di Indonesia - Dahlan, Syafii (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2023)
Abstract According to natural law, humans always live together, live in groups and are not alone. Therefore, according to Aristotle, a Greek philosopher, humans are Zoon Politicon creatures, meaning that humans are creatures who basically always want to socialize and gather with each other, in the sense that humans are creatures who like to socialize and mingle. That’s why humans are also called social creatures. As social creatures, humans need something that can regulate life in the form of a set of rules, this is done so that they do not conflict with each other because of the different needs of each individual. This set of regulations is called law or statute. The laws or laws in Indonesia have changed from time to time until Indonesia declared itself an independent country, a sovereign country. For this reason, here the author wants to reveal the legal journey that has been in force in Indonesia and applied to society or in other terms it is called Indonesian positive law. What about Islamic law? Therefore, this article also describes Islamic law and its application among people who already have beliefs in other religions such as beliefs in animism and dynamism, these two beliefs are shared by Buddhism and Hinduism which came to Indonesia earlier. And over a fairly long period of time, around more than three centuries, there also came adherents of the Christian religion with the understanding of the trinity brought by colonialists from Europe. So Islamic law experienced ups and downs until independence came to Indonesia. keyword: islamic law, implementation